Technical Performance and Clinical Effectiveness of Drop Type With Adjustable Concentrator‐Cell Free and Concentrated Ascites Reinfusion Therapy. Issue 12 (7th June 2017) - Yamada, Yosuke; Harada, Makoto; Yamaguchi, Akinori; Kobayashi, Yasuko; Chino, Takashi; Minowa, Takashi; Kosuge, Takashi; Tsukada, Wataru; Hashimoto, Koji; Kamijo, Yuji
Abstract: Cell‐free and concentrated ascites reinfusion therapy (CART) is a very useful treatment method for refractory ascites but is difficult for many hospitals to employ due to its need for specialized equipment. We have therefore developed drop‐type with adjustable concentrator CART (DC‐CART) that uses a drop‐type filtration mechanism and requires only a simple pump and pressure monitor for its concentration process. Easy adjustment of ascites concentration is possible through a recirculation loop, and filter membrane washing is aided by DC‐CART's external pressure‐type filtration to enable the processing of any quality or quantity of ascites. Moreover, the absence of a roller pump before filtration avoids inflammatory substance release from compressed cells. A total of 268 sessions of DC‐CART using ascites from 98 patients were performed with good clinical results at our hospitals between January 2012 and June 2016. This report presents the detailed methods of DC‐CART and summarizes its clinical effectiveness using patient ascites and blood data obtained from 59 sessions between March 2015 and February 2016. This novel technique successfully processed refractory ascites in numerous diseases with no serious adverse events. DC‐CART could concentrate large amounts of ascites (from median weight: 4900 g [max: 20 200 g] to median weight: 695 g; median concentration ratio: 7.4), and a high amount of protein (median weight: 73 g [max: 294 g]) could be reinfused. Serum albumin levels were significantly increased ( P = 0.010) and kidney function and systemic hemodynamics were well maintained in treated subjects. Additional concentration of ascites and adjustment of ascites volume were easily performed by recirculation (from median weight: 615 g to median weight: 360 g; median concentration ratio: 1.5). Time was needed during DC‐CART for filter membrane cleaning, especially for viscous ascites. Overall, DC‐CART represents a safe and useful treatment method for various forms of refractory ascites that can be performed at a wide range of health care institutions.